KESEIMBANGAN PERLINDUNGAN HUKUM ANTARA DOKTER INTERNSIP DAN PASIEN DALAM KASUS DUGAAN MALPRAKTIK - Emirza Nur Wicaksono (Fakultas Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the balance of legal protection between intern doctors and patients in cases of alleged malpractice within the Indonesian healthcare legal system. The main problem lies in the unclear regulations regarding the legal responsibility of intern doctors, which has the potential to create legal uncertainty and imbalanced protection. This study uses normative legal methods with a statutory and conceptual approach to examine relevant legal norms, principles, and doctrines. The results show that although Law Number 17 of 2023 concerning Health regulates legal protection for medical personnel and patients, there are no specific regulations regarding the legal position of intern doctors. Available dispute resolution mechanisms, whether through mediation, disciplinary bodies, or litigation, do not fully accommodate the characteristics of intern doctors as medical personnel in the learning phase. As a result, uncertainty arises in the division of legal responsibility, resulting in unequal protection. This study concludes that regulatory and institutional strengthening is needed to create a fair and proportional balance of legal protection. These findings contribute to the development of healthcare law and provide a basis for formulating policies that are more responsive to the dynamics of medical practice.